2021
DOI: 10.1016/j.admp.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation du burn-out chez les professionnels de santé des unités de veille sanitaire COVID-19 au Maroc

Abstract: But Le but de cette étude était d’évaluer la prévalence du burnout chez les professionnels de santé travaillant dans les unités de veille sanitaire COVID-19 au Maroc. Méthode Il s’agit d’une étude transversale, descriptive et analytique menée durant deux mois chez 135 professionnels de santé et professionnels d’appuis des unités de veille sanitaire COVID-19 au Maroc. Résultats La majorité (84,44%) des participants était en situation de burn out ; le niveau sévère du burn out a été trouvé … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Indeed, the COVID-19 pandemic has increased workload, guilt, stigma, lack of PPE, and has become a new health care-associated disease that may exacerbate risk factors and promote mental ill health and thus burnout among HCW [21]. In the literature, there is a difference in the prevalence of burnout between countries depending on their economic level.It was higher than those conducted in France (55%) [22] and Iran (53%) [23] and lower than that conducted in Morocco (84.44%) [15]. A global study of 60 countries reported a 51% prevalence of burnout during the COVID-19 pandemic with the highest prevalence in the USA (62%) [8,24].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Indeed, the COVID-19 pandemic has increased workload, guilt, stigma, lack of PPE, and has become a new health care-associated disease that may exacerbate risk factors and promote mental ill health and thus burnout among HCW [21]. In the literature, there is a difference in the prevalence of burnout between countries depending on their economic level.It was higher than those conducted in France (55%) [22] and Iran (53%) [23] and lower than that conducted in Morocco (84.44%) [15]. A global study of 60 countries reported a 51% prevalence of burnout during the COVID-19 pandemic with the highest prevalence in the USA (62%) [8,24].…”
Section: Discussionmentioning
confidence: 69%
“…As various studies [ 18 , 28 ], we found no difference in the predictors of burnout according to age and sex. Others found a higher prevalence of burnout in women and suggest that this is due to their physical and psychological vulnerability, then to a greater emotionality towards the sick and finally, the difficulty of reconciling work and family life [ 15 , 24 ]. Adequate PPE has been widely shown to protect against burnout (RR = 0.88, 95% CI = 0.79–0.97, p = 0.01) [ 24 ]; however, our study did not show an association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 89.14% of the participants in our study reported experiencing burnout, 31.46% of whom had moderate to high burnout. Previous studies have shown that the incidence of burnout among HCWs was up to 84.44% [ 55 ] and that the incidence of moderate to high burnout was 50.13% [ 56 ]. Burnout during the full relaxation of COVID-19 restrictions was much more prevalent but less severe among HCWs than before their relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were significantly associated with a high workload and a low satisfaction with supervisors within working organization. 13 Furthermore, 1 investigation reported a high level of burnout among Moroccan frontline HCWs during the COVID-19 pandemic. 14 To the best of our knowledge, no previous quantitative study has attempted to measure the levels of stress, anxiety, and depression among Moroccan HCWs during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%